Tantangan dan Solusi Etis dalam Transformasi Pembelajaran PAUD Berbasis AI - Sari, Wuni Arum Sekar; Lestari, Briyantika Puji (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2025)
The application of artificial intelligence (AI) in early childhood education (PAUD) holds significant potential to enhance learning but also presents substantial ethical challenges. This study focuses on four key issues: children's data privacy, algorithmic bias in AI, reliance on technology and its impact on social interactions, and the digital divide, which hinder the fair and effective implementation of AI. Using a literature review method, this research integrates analyses from scholarly journals, books, and relevant reports to explore these challenges. The findings reveal that protecting children's data requires stricter regulations; algorithmic bias can be addressed through inclusive design; technology reliance must be balanced with social interaction-based approaches; and the digital divide calls for equitable infrastructure interventions. This study underscores the importance of ethical and strategic approaches in transforming AI-based early childhood education to holistically support children's development.